Predictive Role of Angle of Deviation, QRS Complex RVH, LVH and T Wave Amplitudes in Preeclamptic Pregnant Women in The Third Trimester of Pregnancy - Edebiri O.E; Nwankwo A. A; Akpe P. E; Mbanaso E.L; Obiesi C. N; Chukwu J.A.O (International Journal of Public Health, 2025)
The use of ECG patterns as predictors of preeclampsia offers a promising approach, as it is a widely available and cost-effective tool. Specific ECG patterns, including angle of deviation, QRS Complex (Right Ventricular Hypertrophy (RVH) , Left Ventricular Hypertrophy (LVH)), and T wave amplitudes as a potential tool for predicting preeclampsia. The aim of this study is to investigate the predictive role of angle of deviation, QRS Complex (Right Ventricular Hypertrophy (RVH) , Left Ventricular Hypertrophy (LVH)), and T wave amplitudes in preeclamptic pregnant women during the third trimester. Fourty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. These subjects consisted of twenty (20) normotensive and twenty (20) preeclamptic pregnant women in their third trimester of pregnancy. After the subjects were identified and recruited into the study, they were taken to the laboratory where their vital signs was taken and their ECG patterns recorded with ECG machine. Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. Results from this present study show no significant differences were observed in QRS complex angles related to right ventricular hypertrophy (RVH) between normotensive and preeclamptic pregnant women. Notably, there was a significant increase in QRS complex related to left ventricular hypertrophy (LVH) in preeclamptic pregnant women, indicating left ventricular remodeling's importance. Moreover, there was a significant increase in T wave amplitude, this suggests underlying myocardial electrical remodeling or dysfunction in preeclampsia, emphasizing the need for cardiovascular monitoring. The study underscores the multifactorial nature of cardiovascular changes in preeclampsia and highlights the potential of ECG parameters in aiding early detection.